Correlations between inter group relations and the emergence of stress among farm workers in the rural areas of Sabah, Malaysia - Romzi Ationg; Habibah Artini Ramlie; Mohd. Azri Ibrahim; Mohd Sohaimi Esa; Anna Lynn Abu Bakar (Institute for Promoting Research & Policy Development (IPRPD), 2019)
Inter group relations often considered as the most important factor which brings workers of certain workplace into stressful life. For this reason, this paper presents a discussion on the relationship between inter group relations and stress among workers, in particular the farmers of the rural areas in Sabah, Malaysia. Data were collected through a self-administered questionnaire. In this study, 100 farmers were selected as respondents with a median age of 25. In general, inter group relations reported as had significance relationship with the emergence of stress among farm workers in Sabah, Malaysia. Specifically, the study also found significance relationship between stress among farm workers and group corporation and group conflict. Moreover, based on the findings, in brief, there are also recommended or discusses how we can effectively deal with stress in our daily life